Tribological characterization of electroless NiP coatings lubricated with biolubricants - Ramalho, A. (2007)
Electroless nickel (EN) coatings are used in a wide range of applications concerning their excellent mechanical and tribological properties. The incorporation of solid lubricants, such as polytetrafluoroethylene (PTFE), could even improve the properties of the EN coatings. Above all, we can achieve a film with self-lubricating and excellent anti-sticking characteristics. These uses of electroless nickel coatings are widespread in dry contacts. However, it is well known that in the mechanical components there are a large number of applications that require especially low friction, usually not compatible with the use of unlubricated contacts. Moreover, nowadays, there is a general concern with the environmental impact in the use of lubricants. The tendency is to use fluids with small environmental impact, reducing the contamination made by lubricants of mineral origin. Hence, the aim of the present work was to investigate and improve the understanding of the behaviour of EN and EN + PTFE coatings under lubricated contacts using biolubricants.